Initiation of Green Accounting Based on University Social Responsibility Toward Sustainable University - Yusvita Nena Arinta; Iskandar (JFBA: Journal of Financial and Behavioural Accounting, 2022)
Focusing on sustainable development, universities have a role as a media for the realization of public awareness for the implementation of sustainable values ​​that are integrated into life. At the university, to achieve sustainability, it must integrate the social environment, the natural environment, profit and adherence to religion in a balanced way. The level of understanding of the realization of a sustainable university is through the level of education into corporate social responsibility adopted by the world of social responsibility universities (USR). Green accounting is a reflection of corporate social responsibility and environmental perspectives. This study aims to examine the effect of green accounting initiatives consisting of environmental awareness, environmental involvement, environmental reporting, and environmental audits on the sustainable improvement of universities. The sample in this study were 77 respondents, namely the Top Management of UIN Walisongo and IAIN Salatiga. The data analysis technique used is SPSS. Hypothesis test using regression test. Findings The results of the study that Environmental awareness and Environmental Involvment have a positive and significant effect on Sustainable University. Meanwhile, Environmental Reporting and Environmental Audit have no significant effect on Sustainable University